Prospects and challenges of E-pharmacy in Bangladesh: A perspective on Dhaka city - Mim, Maliha Mehzabin (BRAC University, 2017)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2017.